2013
DOI: 10.1590/s0004-27492013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced retinal injury enhanced neurotrophins secretion and neurotrophic effect of mesenchymal stem cells in vitro

Abstract: Purpose: To investigate neurotrophins expression and neurotrophic effect change in mesenchymal stem cells (MSCs) under different types of stimulation. Methods: Rats were exposed in 10,000 lux white light to develop light-induced retinal injury. Supernatants of homogenized retina (SHR), either from normal or light-injured retina, were used to stimulate MSCs. Quantitative real time for polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA) were conducted for analysis the expression chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Angiogenic factors, such as bFGF and VEGF, could be useful for the treatment of diabetic polyneuropathy. Stem/progenitor cells could have the ability to secrete bFGF and VEGF if transplanted for the treatment of diabetic polyneuropathy .…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenic factors, such as bFGF and VEGF, could be useful for the treatment of diabetic polyneuropathy. Stem/progenitor cells could have the ability to secrete bFGF and VEGF if transplanted for the treatment of diabetic polyneuropathy .…”
Section: Discussionmentioning
confidence: 99%
“…For example, intrinsic BDNF/ cAMP response element-binding protein (CREB) signaling plays an important role against the apoptosis, inflammation, and oxidative stress induced by nicotine-induced neurotoxicity, 17 and endogenous BDNF was reported to increase Bcl-2 protein levels and reduce Bax levels. 18,19 Light-induced retinal injury and some treatments were also shown to promote the intrinsic generation of BDNF and CNTF, which upregulates Bcl-2 and downregulates Bax, 20,21 while the systemic administration of CNTF promoted the neuroprotection of motor neurons through increasing Bcl-2 and decreasing Bax. 22 Moreover, a single intravitreal injection of CNTF protein was found to increase the Bcl-2/Bax ratio in the retina after laser injury to improve cone survival, 23 and single CNTF use protected photoreceptors of animal models with inherited retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Zhang and Wang 81 found that intravitreally injected BM-MSCs could express brain-derived neurotrophic factor (BDNF) and protect the outer nuclear layer in light-damaged retina. Xu et al 29 , 30 also reported that MSCs could secret basic fibroblast growth factor and exhibit neuroprotective effects in light-damaged retina. Importantly, not only intravitreal injection but also intravenous injection of MSC could achieve retinal protective effects.…”
Section: Roles Of Bm-mscs On Retinal Microenvironmental Regulationmentioning
confidence: 99%
“…Xu et al 29 , 30 found that intravitreal injection of BM-MSCs could suppress microglia activation, thereby reducing the retinal injury.…”
Section: Roles Of Bm-mscs On Retinal Microenvironmental Regulationmentioning
confidence: 99%
See 1 more Smart Citation